The Practices of Symbolic Violence on Fashion and Cosmetic Brands - A‘ Ainun Zeva Zachari; Murdianto Murdianto (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the practice of symbolic violence implied in the symbols of fashion and cosmetic brands among college students. This study uses a qualitative descriptive approach to reveal the experiences and views of the subjects in depth. Data were obtained from five students at various universities in Yogyakarta, Indonesia, who were selected as research subjects. Primary data sources were in the form of interviews, observations, and documentation of participants, while secondary data sources were obtained from relevant literature reviews. Data analysis techniques were carried out thematically by reducing data, presenting data, and drawing conclusions. The results of the study indicate that symbolic violence occurs when students from lower-middle socioeconomic groups feel compelled to follow the exclusive brand taste standards set by upper socioeconomic groups. This causes the desire to own certain products even though they are economically unaffordable. Symbolic violence also appears through negative labeling of individuals who do not follow dominant fashion standards, such as the use of the term